Quantitative, Wide-Spectrum Kinase Profiling in Live Cells for Assessing the Effect of Cellular ATP on Target Engagement. Issue 2 (15th February 2018) - Vasta, James D.; Corona, Cesear R.; Wilkinson, Jennifer; Zimprich, Chad A.; Hartnett, James R.; Ingold, Morgan R.; Zimmerman, Kristopher; Machleidt, Thomas; Kirkland, Thomas A.; Huwiler, Kristin G.; Ohana, Rachel Friedman; Slater, Michael; et al.
Summary: For kinase inhibitors, intracellular target selectivity is fundamental to pharmacological mechanism. Although a number of acellular techniques have been developed to measure kinase binding or enzymatic inhibition, such approaches can fail to accurately predict engagement in cells. Here we report the application of an energy transfer technique that enabled the first broad-spectrum, equilibrium-based approach to quantitatively profile target occupancy and compound affinity in live cells. Using this method, we performed a selectivity profiling for clinically relevant kinase inhibitors against 178 full-length kinases, and a mechanistic interrogation of the potency offsets observed between cellular and biochemical analysis. For the multikinase inhibitor crizotinib, our approach accurately predicted cellular potency and revealed improved target selectivity compared with biochemical measurements. Due to cellular ATP, a number of putative crizotinib targets are unexpectedly disengaged in live cells at a clinically relevant drug dose. Graphical Abstract: Highlights: The approach enables quantitative profiling of 178 full-length kinases Compared with biochemical approaches, this is a better predictor of cellular potency An unexpected intracellular selectivity is observed for certain kinase inhibitors A mechanistic analysis of ATP interference on target engagement is performed Abstract : Vasta et al. describe a broad-spectrum approach (BRET) to quantitatively measure target engagement for kinases inside live cells. Compared with biochemical measurements, the analysis revealed an improved intracellular selectivity profile for clinically relevant kinase inhibitors. This serves as a mechanistic tool to determine the effect of cellular ATP on engagement potency.